P13.11 Self-taken extragenital sampling for chlamydia and gonorrhoea in women – is it acceptable? feedback from a self-swab and clinician-swab trial. (13th September 2015) - Wallace, HE; Fisher, J; Daley, S; Harrison, R; Wilson, JD
Abstract : Introduction: Self-taken vulvovaginal swabs analysed by nucleic acid amplification tests (NAATs) for chlamydia and gonorrhoea are standard practice worldwide. Extra-genital sampling (rectum and pharynx) is becoming increasingly important in women, with evidence that urogenital sampling alone may miss infections. Yet, little is known about women's views of extra-genital sampling. We explored the acceptability of self-taken extra-genital samples for women as part of a clinician versus self-taken extra-genital sampling study. Methods: Women attending a sexual health clinic were invited to participate in a 'swab yourself' trial. After randomisation, both clinician and self-taken samples for chlamydia and gonorrhoea NAATs from vulvovaginal, pharyngeal and rectal sites were taken. Participants were then invited to complete a questionnaire about the extra-genital sampling. Results: 400 surveys were returned from 402 women recruited (response rate >99%), age range 17–57 (mean 25.2) years. 75% disagreed/strongly disagreed with the statement 'taking my own samples was difficult'. 72% agreed/strongly agreed that they felt confident taking their own swabs but 30.5% agreed/strongly agreed they felt uncomfortable taking their own swabs; of these 53 (43%) stated they had never had anal sex. 42% agreed/strongly agreed that they would prefer to take their own samples compared to 34% who agreed/strongly agreed they would prefer clinician-taken swabs. 66% agreed/strongly agreed they would be happy to take the samples themselves in a non-clinic setting. Free comments covered themes of 'more confidence if had clinician samples taken before', 'concerns if self-swabbing would give correct results'. Nine commented specifically on discomfort, but none disagreed with the statement 'I would be happy to take my own swabs in a non-clinic environment'. Conclusion: Extra-genital sampling was highly acceptable to the majority of women, with high levels of confidence and low reports of discomfort. This has positive implications for the future of extra-genital testing in women, especially in non-clinic settings. Disclosure of interest statement: Dr Janet Wilson has received honoraria and travel and accommodation expenses from BD Diagnostics, and research grants in the form of diagnostic kits from Hologic/Gen-Probe.